AN IN SILICO APPROACH TO ANALYZE HCV GENOTYPE‑SPECIFC BINDING‑SITE VARIATION AND ITS EFECT ON DRUG–PROTEIN INTERACTION - Khalid, Ramsha; Anwar, Muhammad Faraz; Raees, Muhammad Aanish; Naeem, Sadaf; Abidi, Syed Hani; Ali, Syed (Nature Research, 2020)
Genotype variation in viruses can afect the response of antiviral treatment. Several studies have established approaches to determine genotype-specifc variations; however, analyses to determine the efect of these variations on drug–protein interactions remain unraveled. We present an in-silico approach to explore genotype-specifc variations and their efect on drug–protein interaction. We have used HCV NS3 helicase and fuoroquinolones as a model for drug–protein interaction and have investigated the efect of amino acid variations in HCV NS3 of genotype 1a, 1b, 2b and 3a on NS3fuoroquinolone interaction. We retrieved 687, 667, 101 and 248 nucleotide sequences of HCV NS3 genotypes 1a, 1b, 2b, and 3a, respectively, and translated these into amino acid sequences and used for genotype variation analysis, and also to construct 3D protein models for 2b and 3a genotypes. For 1a and 1b, crystal structures were used. Drug–protein interactions were determined using molecular docking analyses. Our results revealed that individual genotype-specifc HCV NS3 showed substantial sequence heterogeneity that resulted in variations in docking interactions. We believe that our approach can be extrapolated to include other viruses to study the clinical signifcance of genotypespecifc variations in drug–protein interactions.
Keywords: Type of access: Open Access; genotype; drug–protein interaction